Assessment of knowledge and skills training needs among employed midwives in health and medical centers, compared to expected duties as a part of Health System Reform Program, 2019 - Zahra Enteshari; Nikoo Yamani; Athar Omid (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: As a part of healthcare providers of the Health System Reform Program, midwives are required to master the necessary knowledge and skills to meet the related demands of society. This study was aimed to assess the knowledge and skills training needs of practicing midwives of health and medical centers of Isfahan. METHODS: This study is a descriptive cross-sectional study. The statistical target population was midwifery experts working in Isfahan health centers and the samples were selected through simple random sampling (sample size 250). Data were collected by two questionnaires to assess knowledge and skill needs. The validity of the questionnaires was confirmed by experts of the province and city health centers and medical education experts and its reliability was calculated by Cronbach's alpha (98%). Data were analyzed using SPSS 23 software and descriptive and analytical statistical methods (frequency, mean, variance). RESULTS: The first five knowledge training priorities of employed midwives in health and medical centers, which comprise most of the means values, are pregnancy complications and abnormalities (3.64 ± 1.21); mammography and its interpretation (64.3 ± 1.30); skills and principles of parenting (3.59 ± 1.24); shortness of breath and palpitations during pregnancy (3.58 ± 1.16); and common mental disorders (3.57 ± 1.16). The most important skills training needs were Excel (1.21 ± 3.59), PowerPoint (27.1 ± 54.3), internet (3.52 ± 1.25), and parameters registration and reporting in the SIB system (3.49 ± 1.28). Employed midwives of the health and medical centers displayed a significant difference in feeling the need for training in some subjects. CONCLUSION: Needs assessment is the foundation of purposeful training, and better training leads to improved performance of personnel and organizations. Therefore, it is imperative that reliable and documented data be utilized for promotion and improvement of in-service training programs of employed midwives of the health and medical centers of Isfahan province and also for revising university curriculums. Taking these measures would lead to the empowerment of personnel and general development of society.